Reading-comprehension of popularization scientific texts in a non-Francophone context: the challenges of digital technology - MEHYAOUI , Adila (Journal of Human Sciences, 2023)
In this article, our interest relates to the potential of technological developments which aim to integrate the digital format of popularized scientific texts. From our previous research, we want to continue our work allowing us to better exploit the results obtained concerning the integration of an interactive reading approach using digital technology to better motivate and empower learners at university. Without intending to promote the passing fad of all-digital, we want to evaluate the importance of the use of both paper and digital media of scientific popularization texts in the didactic approach which aims to diversify reading activities in the French language and consequently improve reading comprehension among future Arabic-speaking engineers.